KNOWLEDGE AND PRACTICE OF NURSES ABOUT PATIENT SAFETY IN 105 HOSPITAL IN 2021 (Vietnam Journal of Community Medicine, 2022)
A cross-sectional study was conducted to describe the current status of knowledge and practice in patient safety among 300 nurses in 105 Hospital in 2021. The results showed that: Knowledge: Percentage of nurses achieving knowledge medical incidents is 36.0%, knowledge of medical incident prevention is 52.0%, knowledge of medical incidents in 105 Hospital is 40.0%. The percentage of nurses with general knowledge of patient safety is 29.7%. About the practice: 27.1% of nurses have practice on patient safety content. The research results contribute to improving the quality management for the hospital.
Keywords: Patient safety, 105 hospital.